Penyuluhan Apakah Kanker Serviks Itu Pada Ibu Dan Remaja Putri Di Desa Nagrak - Ciangsana, Bogor. - Atut Cicih Mayasari; Lily Marliany Surjadi; Laksmi Maharani; Deasyka Yastani (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Cervical cancer is the second leading cause of death in women. Yet, cervical cancer is preventable because it is caused by the Human Papilloma Virus (HPV), which, if infected, can take decades to develop into cancer. Cervical cancer prevention efforts have not yet reached their target. Coverage remains low. Knowledge about cervical cancer itself is still lacking, as is prevention. The perceived discomfort of early detection tests makes women reluctant to undergo them. Therefore, education about cervical cancer is needed to increase knowledge and thus increase the coverage of early detection tests. The ultimate goal is to reduce the incidence and mortality caused by cervical cancer. To this end, education about cervical cancer is being conducted for women, namely mothers and young girls, especially in the villages of Nagrak and Ciangsana, Bogor.